Definition of Tweener: Consensus Among Experts in Treating Early-onset Scoliosis. Issue 3 (12th March 2023) - Quan, Theodore; Matsumoto, Hiroko; Bonsignore-Opp, Lisa; Ramo, Brandon; Murphy, Robert F.; Brooks, Jaysson T.; Welborn, Michelle C.; Emans, John B.; Anari, Jason B.; Johnston, Charles E.; Akbarnia, Behrooz A.; McCarthy, Richard; et al.
Abstract : Background: The term "Tweener" is colloquially used to refer to early-onset scoliosis (EOS) patients whose age and development make them candidates for multiple surgical options. The purpose of this study was to establish expert consensus on a definition to formally characterize the Tweener population. Methods: A 3-round survey of surgeons in an international EOS study group was conducted. Surgeons were provided with various patient characteristics and asked if each was part of their definition for Tweener patients. Responses were analyzed for consensus (≥70%), near-consensus (60% to 69%), and no consensus (<60%). Results: Consensus was reached (89% of respondents) for including chronological age in the Tweener definition; 8 to 10 years for females and 9 to 11 years for males. Surgeons agreed for inclusion of Sanders score, particularly Sanders 2 (86.0%). Patients who have reached Sanders 4, postmenarche, or have closed triradiate cartilage should not be considered Tweeners. Bone age range of 8 years and 10 months to 10 years and 10 months for females (12 y for males) could be part of the Tweener definition. Conclusions: This study suggests that the Tweener definition could be the following: patients with open triradiate cartilage who are not postmenarche and have not reached Sanders 4, and if they have one of the following: Sanders 2 or chronological age 8 to 10 years for females (9 to 11 y for males) or bone age 8 years and 10 months to 10 years and 10 months for females (12 y for males). This definition will allow for more focused and comparative research on this population. Level of Evidence: Level V—expert opinion.